2021
DOI: 10.1039/d1gc01021b
|View full text |Cite
|
Sign up to set email alerts
|

Protein from renewable resources: mycoprotein production from agricultural residues

Abstract: Globally, one in nine people suffer from undernourishment with evidence that this number is increasing. Additionally, due to the projected 50% increase in global population, the demand in worldwide animal-sourced...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…An ethanol plant producing 43,000 tons of ethanol per year was estimated to be capable of producing 39,000 tons of fungal biomass per year with a capital cost of $50 million and a payback period of about 4.5 years. Similarly, Upcraft et al (2021) performed technoeconomic and lifecycle assessments (LCA) of producing mycoprotein (F. venenatum) using agricultural lignocellulosic residues (rice straw) as feedstock. Various rice straw residues were treated with food-grade ionic liquids in combination with food-grade cellulase enzymes to produce fermentable sugars that were then fed into the corn mycoprotein production process.…”
Section: Economics Of Microalgae-and Filamentous Fungi-based Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An ethanol plant producing 43,000 tons of ethanol per year was estimated to be capable of producing 39,000 tons of fungal biomass per year with a capital cost of $50 million and a payback period of about 4.5 years. Similarly, Upcraft et al (2021) performed technoeconomic and lifecycle assessments (LCA) of producing mycoprotein (F. venenatum) using agricultural lignocellulosic residues (rice straw) as feedstock. Various rice straw residues were treated with food-grade ionic liquids in combination with food-grade cellulase enzymes to produce fermentable sugars that were then fed into the corn mycoprotein production process.…”
Section: Economics Of Microalgae-and Filamentous Fungi-based Foodsmentioning
confidence: 99%
“…Filamentous fungi have been utilized in food products, especially as mycoprotein. Upcraft et al (2021) presented the results of an LCA of mycoprotein produced from lignocellulosic residues such as rice straw, corn stover, switchgrass, or miscanthus. The results of the LCA demonstrated significant reductions in global warming potential, terrestrial acidification, freshwater eutrophication, and arable land use compared to traditional beef protein.…”
Section: Environmental Impacts Of Filamentous Fungi-based Foodsmentioning
confidence: 99%
“…In addition to the optimization of the actual cell-cultivation processes, the sources of the inputs make a large contribution to the environmental impacts. In particular, the possibilities of utilizing side-streams from agriculture and food processing as nutrient sources for cell-culturing processes can provide environmental benefits 7,19 . Extracting glucose and amino acids directly from side-streams would for increasing the renewable energy production capacity according to the global needs 12 .…”
Section: Future Potentialmentioning
confidence: 99%
“…We found that the protein content increased to 45%, indicating that medium composition deeply affects the protein content of yeast biomass. By using a rich medium, the protein content of D. hansenii Mo40 was comparable to well established meat alternatives such as Quorn by Fusarium venenatum [38] and oncom by Neurospora intermedia [39]. In order to evaluate the ability to produce SCO, D. hansenii Mo40 cells were cultured on lipidogenic medium characterized by low nitrogen content, known to induce lipids accumulation [27].…”
Section: Scp and Sco Productionmentioning
confidence: 99%